Neuroprotective effects of isoflurane against lipopolysaccharide-induced neuroinflammation in BV2 microglial cells by regulating HMGB1/TLRs pathway - Han, Degang; Zhou, Zheng; Liu, Jingpeng; Wang, Tingting; Yin, Jinbo (Folia Neuropathologica, 2020)
Microglia, as the first line of defence of the central nervous system (CNS), has a major role in inflammatory response. It was reported that isoflurane has a neuroprotective role in the pathological process of CNS by interfering with inflammatory response. While the mechanism and function of isoflurane in microglia-mediated inflammation are still not clearly articulated. In our study, the inflammation model was established by the activation of lipopolysaccharide (LPS) in BV2 cells in vitro. The results demonstrated that isoflurane inhibited the release of nitric oxide (NO) and enhanced the survival of BV2 cells, meanwhile, isoflurane reduced the levels of inflammatory factors and downregulated the expressions of inflammation-related genes and proteins in LPS-mediated BV2 cells. Furthermore, we demonstrated that overexpression of high-mobility group box 1 protein (HMGB1) could reverse the reduction in NO concentration, enhancement of cell BV2 viability and inhibition of inflammatory response, which were mediated by isoflurane in LPS-induced BV2 cells. Therefore, we suggested that isoflurane inhibits the activation of LPS-induced neuro microglia and reduces the release of inflammatory factors by regulating HMGB1, suggesting that isoflurane might play a protective role in LPS-induced neuroinflammation through the HMGB1 pathway.